2021
DOI: 10.3389/fpsyg.2020.604397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Support on the Psychological Adjustment of Chinese Left-Behind Rural Children: A Moderated Mediation Model

Abstract: There are tens of millions of children left behind by one or both rural-to-urban migrant parents (left-behind children, LBC) in rural China. Compared to non-left-behind children (NLBC), LBC are disadvantaged in psychological adjustment. Research has shown social support can help LBC grow up healthily, but the plausible mechanisms linking support to adjustment remain unclear. The present study investigated the mediating role of basic psychological need satisfaction (BPNS) in the above relationship, as well as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…Previous studies have reported correlations among social support, psychological resilience and health in Asian cultures 7,22,[62][63][64] (i.e. South Korea, Japan and Singapore), which implies the importance of social support in the non-Western cultures 65 . Moreover, the current finding implies that the number of social support providers plays an important role in mediating the relationship between mental state and resilience, implying the importance of social support in mental health 66,67 .…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported correlations among social support, psychological resilience and health in Asian cultures 7,22,[62][63][64] (i.e. South Korea, Japan and Singapore), which implies the importance of social support in the non-Western cultures 65 . Moreover, the current finding implies that the number of social support providers plays an important role in mediating the relationship between mental state and resilience, implying the importance of social support in mental health 66,67 .…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, the findings were found in a study sample of Chinese children. For example, Fan and Fan found that higher levels of resilience could reduce the psychological adjustment difficulties (e.g., depression, loneliness, self-esteem) among Chinese left-behind children ( 42 ). They identified resilience as a quality necessary for the growth of children in adversity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that a mother’s care can contribute to the development of a careful and sensitive personality in children, while a father’s care was crucial in fostering an independent and strong personality, which was associated with aggression development . Moreover, migrating fathers were also associated with providing less warmth and emotional support than migrating mothers . Third, an initial separation at adolescence from 1 or both parents was more strongly associated with total aggression and/or PA than separation at school age and/or preschool age.…”
Section: Discussionmentioning
confidence: 87%